Modelling of bread dough aeration during mixing: Experimental investigations using scale-up mixers - Chin, Nyuk Ling; Campbell, G. M. (The Institution of Engineers, Malaysia, 2011)
Link to publisher's homepage at http://www.myiem.org.my/